Abnormal uterine bleeding in adolescence - Samal, Sunita; Vishalakshi, Ashwini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Abnormal uterine bleeding (AUB), which is defined as excessively heavy, prolonged and/or frequent bleeding of uterine origin, is a frequent cause of visits to the Emergency Department and/or health care provider. While there are many etiologies of AUB, the one most likely among otherwise healthy adolescents is dysfunctional uterine bleeding (DUB), which is characterizing any AUB when all possible underlying pathologic causes have been previously excluded. The most common cause of DUB in adolescence is anovulation, which is very frequent in the first 2-3 post-menarchal years and is associated with immaturity of the hypothalamic-pituitary-ovarian axis. Management of AUB is based on the underlying etiology and the severity of the bleeding and primary goals are prevention of complications, such as anemia and reestablishment of regular cyclical bleeding, while the management of DUB can in part be directed by the amount of flow, the degree of associated anemia, as well as patient and family comfort with different treatment modalities. Treatment options for DUB are: combined oral contraceptives (COCs), progestogens, non-steroidal anti-inflammatory drugs (NSAIDs), tranexamic acid (anti-fibrinolytic), GnRH analogues, Danazol and Levonorgestrel releasing intra uterine system (LNG IUS).